Advancing Our Knowledge of Cognition in Disorders of Consciousness: A Critical Revisit - Po-Tso Lin; Hsiang-Yu Yu (Acta Neurologica Taiwanica)
This narrative review aims to elucidate an emerging state of consciousness termed “cognitive-motor dissociation (CMD),” characterized by brain activity patterns closely resembling those observed in healthy individuals. This distinctive phenomenon is notably evident in patients diagnosed with comatose states, unresponsive wakefulness states, or minimally conscious states. Employing functional magnetic resonance imaging or electroencephalography holds promise for identifying CMD. The emergence of CMD not only introduces a fresh conceptual framework but also provides valuable predictive insights into outcomes and prognoses for individuals with disorders of consciousness. However, the recognition of CMD raises ethical considerations, particularly in evaluating the decision-making capacity regarding life-or-death choices for individuals in this state. Therefore, it is crucial to advocate for further scientific and comprehensive research to enhance our understanding of CMD and navigate its nuanced complexities.